COATING SYSTEM AND COATING METHOD - KOHLHAGEN, Tobias; HENNINGER, Christoph; FERRER, Franziska; HESS, Harald (2023)
The invention relates to a coating system and a method for coating a running web, in particular a paper or cardboard web, with a coating medium, comprising a roller and an application head for applying the coating medium onto the roller, and a treatment nip for transferring the coating medium from the roller onto the web, wherein the treatment nip is formed by the roller and a counter element, and wherein, when seen in the rotational direction of the roller, an applicator is arranged between the application head and the treatment nip in order to subject the coating medium on the roller to vapor and/or air.